Pengukuran Efekivitas Iklan Gojek Menggunakan Metode Epic Model di Kalangan Mahasiswa - Azri Wajihan Mahdi; Diana Triwardhani; Heni Nastiti (Jurnal Manajemen dan Inovasi (MANOVA), 2022)
This research is a descriptive quantitative study that aims to find out how effective Gojek's online advertising is for students living in Jakarta using the EPIC Model method. The sample in this study used 100 active students residing in Jakarta as respondents. Sample selection was done by purposive sampling method with non-probability sampling technique. In this study, measurements will be carried out on the 4 dimensions of EPIC by looking for the average score of each dimension, the results of the study show the empathy dimension makes advertising able to attract customers' attention, the dimension of persuasion that advertising can affect customers, the impact dimension makes the advertisement give a deep impression to the customer, and the communication dimension can be stated that Gojek advertising can be well remembered and understood. From the results of the EPIC Rate of the four dimensions, the average EPIC score indicates the effective category.